Secondary School Dropout in Tanzania: Evidence from Uyui District in Tabora Region (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2025)
Dropout has remained a major concern in Tanzania’s education sector for several years, undermining national efforts to achieve equitable access to quality secondary school education. The study investigated the key factors contributing to secondary school student dropout in the Uyui-Tabora region in Tanzania. It examined the influence of school-related, student-related, and parent-related factors using a mixed-methods approach and an explanatory research design. Data were collected from 180 respondents (students, teachers, and parents) using structured questionnaires, while interviews were conducted with five school heads. Quantitative data were analysed using descriptive and inferential statistics, including multiple linear regression, while qualitative data underwent content analysis. Findings showed a significant relationship between dropout rates and school-, student-, and parent-based factors. School-related factors had the strongest influence (B = 0.112, p = .032), indicating that poor conditions such as lack of hostels, harsh discipline, and inadequate resources contribute significantly to dropout. Student-related factors (B = 0.038, p = .021), including peer pressure and unethical behaviour, and parent-related factors (B = 0.052, p = .028), such as poverty, alcoholism, and parental neglect, were also significant predictors. The study concluded that negative school environments, including teacher shortages, poor infrastructure, and limited learning materials, play a central role in student dropout. Additionally, student behaviours influenced by peer and cultural pressures, and lack of basic necessities like uniforms, contribute to the problem. Parental issues such as poverty, substance abuse, and negative attitudes toward education further exacerbate dropout rates. The findings underscore the need for integrated policy responses. The Ministry of Education, local authorities, and communities must work together to improve school infrastructure, support families, and implement learnercentred programmes. Addressing these multi-faceted challenges is vital to reducing dropout rates and ensuring equitable access to quality education in Tanzania.